Age-depth model of an Antarctic snow petrel stomach oil deposit - Mark A Stevenson; Dominic A Hodgson; Michael J Bentley; Darren R Gröcke; Neil Tunstall; Chris Longley; Alice Graham; Erin L McClymont (PANGAEA, 2025)
Organic geochemistry, stable isotope analysis and elemental scans are presented here from a stomach-oil deposit collected at Heimefrontfjella Range, Dronning Maud Land, East Antarctica. Stomach-oil deposit 3012MUM2 was collected in season 2014–15 from the Boysennuten nunatak in the Heimefrontfjella Range of East Antarctica (74° 34.14 extquotesingleS; 11° 15.02 extquotesingleW). The aim of the analysis is to investigate snow petrel diet during the Holocene and in turn to infer changing sea-ice conditions in the Weddell Sea and South Atlantic sector of the Southern Ocean (Stevenson et al., Climate of the Past Discussions). The data include results from non-destructive XRF scanning, fatty acid distributions and other biomarkers of productivity and diet (Department of Geography, Durham University, Durham, U.K.) and bulk stable carbon and nitrogen isotope ratios (Department of Earth Sciences, Durham University, Durham, U.K.). The age-depth model is constrained by 12 new bulk radiocarbon measurements (Beta Analytic Inc., Miami; SUERC, Glasgow).
In: Stevenson, MA et al. (2025): Mid-Holocene sea-ice dynamics and climate in the northeastern Weddell Sea inferred from an Antarctic snow petrel stomach oil deposit [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.980519